Qualitative analysis on mathematical literacy ability and student responsibility with realistic mathematics education learning models of ethnomathematics nuance - Kurniati, Chrisvonela Neri; Mariani, Scolastika (Unnes Journal of Mathematics Education, 2020)
The purpose of this research is to know the ability of mathematical literacy and the responsibility of students with an ethnomathematics-style Realistic Mathematics Education learning model. This type of research is a qualitative research that is descriptive. To establish the validity of qualitative data then the inspection techniques used in this research using the triangulation of the source, that is to compare the suitability of data obtained from the results of interviews and tests. The study was conducted on one of the junior high schools in Semarang, and there are 6 research subjects representing each of the 2 students for the group of high responsibility categories, 2 students for the category of medium responsibility groups, and 2 students for the group of low liability categories. In this study it was found that there were students representing the responsibilities of being granted results from mathematical literacy skills tests with the same results as students representing high responsibility groups. The factors influencing the findings are the thoroughness of the students representing the group of responsibilities being in Corrected their work.